Factors associated with risky sexual behaviors among undergraduate students in Thailand - Jintapa Benchamas; Nopparat Senahad; Natnapa Heebkaew Padchasuwan; Pokkamol Laoraksawong; Surachai Phimha; Pannee Banchonhattakit (BMC, 2024)
Abstract Background Risky sexual behaviors refer to actions or practices that increase the likelihood engaging in sexual intercourse. Such behavior can lead to HIV infection/AIDS, sexually transmitted diseases, and unintended pregnancy. The impact of risky sexual behaviors is a growing public health concern. These issues pose significant challenges to public health, particularly among university students and younger age groups who may be more vulnerable to various factors. Thus, this research aimed to examine the factors and sexual health literacy associated with risky sexual behaviors among undergraduate students in the four major regions of Thailand. Method A cross-sectional study was conducted among 916 undergraduate students in their final semester of the 2023 academic year, from March to May 2024, at public, autonomous, and private universities across four regions: northern, central, southern, and northeastern of Thailand. The study employed multistage random sampling method. A self-administered structured questionnaire was used to assess risky sexual behaviors and the data were analyzed using multiple logistic regression. Results A total of 916 students participated in the study. The prevalence of risky sexual behavior was 46.84% (95% CI:43.56% to 50.12%) students engaged in risky sexual behaviors. Risky sexual behavior was significantly associated with grade point averages (GPA) between 2.00-3.00 could protective risky sexual behaviors was 42% as compared to GPA > 3.00 (AOR = 0.58, 95%CI:0.42 to 0.79), ex-substance use (AOR = 3.48, 95%CI:1.46 to 8.26), Current smoker (AOR = 2.90, 95%CI:1.90 to 4.43), negative attitudes toward risky sexual behaviors (AOR = 2.32, 95%CI:1.32 to 4.06), access to places of ill repute and access to sexual arousal stimuli (sometime) (AOR = 2.23, 95%CI:1.41 to 3.52), social influences (high level) (AOR = 0.29, 95%CI:0.15 to 0.55), and sufficient to excellent level of the application of information about sexual health (AOR = 0.48, 95%CI:0.26 to 0.87) of statistical significance at P < 0.05, which was significantly associated with risky sexual behavior. Conclusion The findings of this study offer important insights for preventing risky sexual behaviors among undergraduate students across four regions. By promoting healthy sexual practices and encouraging behavior modification, negative consequences can be reduced. Public health care providers, policymakers, and stakeholders should implement tailored strategies, such as comprehensive sexual education and accessible health services, to address the specific needs of these students. These targeted interventions can significantly reduce the prevalence of risky sexual behaviors.